2019
DOI: 10.26794/1999-849x-2019-12-3-48-58
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Federal Budgetary Investments in Ensuring the Socio-Economic Development of Russia in 2019–2021

Abstract: The paper describes the specifics of planning federal budget allocations for budgetary investments in 2019–2021.The relevance of the paper is due to the fact that Presidential Decree No. 204 of May 07.2018 sets the goal for Russia to break into the top five world economies and ensure economic growth rates exceeding the world rates while maintaining the macroeconomic stability. The subject of the research is federal budget allocations for budgetary investments. The purpose of the research was to assess the volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Research by foreign authors has shown that not only private but also public investment has a positive impact on GDP. For example, in the United States, the multiplier effect of budget investments was 1.92 in the short term and 3.21 in the long term [1]. In India, the amount of state funding for national projects is 90%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by foreign authors has shown that not only private but also public investment has a positive impact on GDP. For example, in the United States, the multiplier effect of budget investments was 1.92 in the short term and 3.21 in the long term [1]. In India, the amount of state funding for national projects is 90%.…”
Section: Introductionmentioning
confidence: 99%
“…Issues of budget financing of investments are widely covered in the works of modern scientists and economists. For example, R. A. Alandarov [1,4] analyses the role of Federal budget investments in the socio-economic development of the Russian Federation and assesses the quality of financial management of budget investments in the country; A. A. Derkach [5] studies the formation of the investment social budget to Finance capital investments in the social sector; O. V. Kiseleva [6] reveals the role of budget financing in the investment policy of the Russian Federation; Kuznetsova [7,8] devoted to Federal support for investment in Russia and problems of their evaluation; V. Arbatskaya [3] covers the legal aspects of investment budget expenditures; V. N. Adronova and D. O. Maslakova in his work [9] compare the regions of the Russian Federation in terms of investment financing, including budgetary funds; in T. V. Shchukina [10] and L. A. Michalinos [11] provides an analytical analysis of the development budget investments in the territory of the Russian Federation; O. Ivanov and E. M. Buchwald [12] covers in detail the investment priorities of the Russian Federation on a strategic level.…”
Section: Introductionmentioning
confidence: 99%